Isopentyl butanoate: aggregation pheromone of the brown spiny bug, Clavigralla Tomentosicollis (hemiptera: coreidae), and kairomone for the egg parasitoid gryon sp. (hymenoptera: scelionidae) - Kpongbe, H.; Berg, J. van den; Khamis, F.; Tamò, Manuele; Torto, B. (Springer, 2019)
The brown spiny bug, Clavigralla tomentosicollis Stål (Hemiptera: Coreidae) is a key pest of leguminous crops in many countries in Africa, causing significant yield losses especially in cowpea, pigeon pea and common beans. Although C. tomentosicollis uses olfaction to aggregate, little is known about the identity of the aggregation pheromone. This study aimed to identify the aggregation pheromone of C. tomentosicollis and to test its potential role in the behavior of its egg parasitoid, Gryon sp. In Y-tube olfactometer bioassays, only male volatiles strongly attracted both sexes of C. tomentosicollis. Coupled gas chromatography/electroantennographic detection (GC/EAD) and GC/mass spectrometry were used to identify antennally-active compounds from male volatiles. Antennae of both sexes detected identical components including a male-specific component, identified as isopentyl butanoate, which was also detected by antenna of the egg parasitoid. In olfactometer bioassays, both sexes of C. tomentosicollis and the egg parasitoid responded to isopentyl butanoate. These results suggest that isopentyl butanoate serves as an aggregation pheromone for both sexes of C. tomentosicollis and a useful kairomone to attract the parasitoid in the management of C. tomentosicollis.